2015
DOI: 10.1007/s00299-015-1802-0
|View full text |Cite
|
Sign up to set email alerts
|

ROS-induced oxidative stress and apoptosis-like event directly affect the cell viability of cryopreserved embryogenic callus in Agapanthus praecox

Abstract: Oxidative stress and apoptosis-like programmed cell death, induced in part by H 2 O 2 , are two key factors that damage cells during plant cryopreservation. Their inhibition can improve cell viability. We hypothesized that oxidative stress and apoptosis-like event induced by ROS seriously impact plant cell viability during cryopreservation. This study documented changes in cell morphology and ultrastructure, and detected dynamic changes in ROS components (O 2 (·-) , H2O2 and OH·), antioxidant systems, and prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 60 publications
1
52
0
1
Order By: Relevance
“…Photoinhibition not only decreases the photosynthetic ratio but also induces production of reactive oxygen species (ROS), and these lead to oxygen stress. Membranes can be damaged by excessive ROS, resulting in cell dysfunction such as the depression of membrane transport function and the membrane-associated enzyme activity (Zhan et al, 2014; Zhang et al, 2015a). To enhance plant tolerance to chilling and thus improve crop productivity, application of exogenous substances has been used widely (Shuming et al, 2012; Yang et al, 2015; Han et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Photoinhibition not only decreases the photosynthetic ratio but also induces production of reactive oxygen species (ROS), and these lead to oxygen stress. Membranes can be damaged by excessive ROS, resulting in cell dysfunction such as the depression of membrane transport function and the membrane-associated enzyme activity (Zhan et al, 2014; Zhang et al, 2015a). To enhance plant tolerance to chilling and thus improve crop productivity, application of exogenous substances has been used widely (Shuming et al, 2012; Yang et al, 2015; Han et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Chua and Normah (2011) also reported that applying 0.28 mM AsA in the LS step could slightly enhance the survival percentage (3.3%) of pulasan shoot tips (Nephelium rumboutanake). The oxidative stress during callus cryopreservation of Agapanthus praecox was determined by Zhang et al (2015). It was found that the ROS-induced oxida- preconditioned on PGR-free MVW containing 0.1 M sucrose (six days) and then transferred to PGR-free MVW containing 0.1 M sucrose and 0.1 mM ascorbic acid (one day).…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis has some support from other studies. It has been reported that the DAD1 gene was up-regulated in callus cells of Agapanthus praecox during the recovery stage following inoculation into fresh medium after cryopreservation (Zhang et al, 2015). It was important to know the expression change of these genes (Fig.…”
Section: Discussionmentioning
confidence: 99%